Implikasi Hukum Undang-Undang Nomor 6 Tahun 2014 Tentang Desa Terhadap Eksistensi Negeri Di Kabupaten Maluku Tengah - Pattinasarany, Yohanes; Pattipawae, Dezonda Rosiana; Lainsamputty, Natanel (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: The consequences of the enactment of Law no. 6/2014, requires legal adjustments to be made at the regional level of Central Maluku Regency, as a basis for administering state government, one of which is related to the designation of the State as a traditional village.  UU no. 6/2014 requires the regional government of Central Maluku district to organize the customary law community unit and declare it a state with the legal form of regional regulations as stipulated in Article 98 paragraph (1) of Law no. 6/2014 which regulates that Traditional Villages are determined by Regency/City Regional Regulations.Purposes of Devotion: This Community Service is in order to provide input and solutions as well as legal education, especially regarding the Legal Implications of Law Number 6 of 2014 concerning Villages on State Existence in Central Maluku Regency, including Hatumete State, Tehoru District, Central Maluku Regency, Maluku Province. Method of Devotion: The method used is legal counseling to the community and action to villages and customary villages that are partners in service.Results of the Devotion: Legal implications of Law no. 6 of 2014 regarding the countries in Central Maluku district, including Hotumesse Country, requires legal legalization of the existence of the country as a form of traditional village whose governance system is based on origin rights and customary law. Structuring the customary law community unit by paying attention to: (a) the history of the Customary Law Community; (b) Indigenous territories; (c) Customary law; (d) assets and/or customary objects; and (e) traditional government institutions/systems. The act of structuring customary law community units as an instrument for establishing the country as a form of traditional village whose extension is recognized through Law no. 6 of 2014. However, the state government and state saniri as well as the people of Hotumesse State do not yet have an understanding of the rights and authority of the State or traditional villages as regulated by Law no. 6 of 2014.